Herbal supplements: Research findings and safety. Issue 5 (17th May 2018) - Pruitt, Rosanne; Lemanski, Ashley; Carroll, Adam
Abstract : Abstract: Herbal supplements are used extensively worldwide without much awareness regarding their safety and efficacy. Extensive research to determine the safety, utility, and level of research support for commonly used herbs has culminated in an easily accessible summary chart for NP providers. Abstract : Herbal supplements are used extensively worldwide without much awareness regarding their safety and efficacy. Extensive research to determine the safety, utility, and level of research support for commonly used herbs has culminated in an easily accessible summary chart for NPs.